Usability and accessibility of aging/health-related web sites - Zaphiris, Panayiotis; Kurniawan, Sri Hastuti (My University, 2001)
This study is aimed at answering whether aging/health-related web sites of different domain extensions (i.e. .com, .edu, .gov and .org) differ in their accessibility and usability, and whether these two measures are correlated. The usability and accessibility of governmental, organizational, educational and commercial aging/health-related web sites were compared using two automatic evaluation tools: Bobby and LIFT. The governmental web site group has the highest compliance with Web site Content Accessibility Guide although only 52% got an approved status. The accessibility approval was found to correlate significantly with overall usability ratings for all groups, except the commercial web site group.